Rac1 and Rac2 GTPases are necessary for early erythropoietic expansion in the bone marrow but not in the spleen - Kalfa, Theodosia A. (Ferrata Storti Foundation, 2010)
BACKGROUND: The small Rho GTPases Rac1 and Rac2 have both overlapping and distinct roles in actin organization, cell survival, and proliferation in various hematopoietic cell lineages. The role of these Rac GTPases in erythropoiesis has not yet been fully elucidated. DESIGN AND METHODS: Cre-recombinase-induced deletion of Rac1 genomic sequence was accomplished on a Rac2-null genetic background, in mouse hematopoietic cells in vivo. The erythroid progenitors and precursors in the bone marrow and spleen of these genetically engineered animals were evaluated by colony assays and flow cytometry. Apoptosis and proliferation of the different stages of erythroid progenitors and precursors were evaluated by flow cytometry. RESULTS: Erythropoiesis in Rac1(−/−);Rac2(−/−) mice is characterized by abnormal burst-forming unit-erythroid colony morphology and decreased numbers of megakaryocyte-erythrocyte progenitors, erythroid colony-forming units, and erythroblasts in the bone marrow. In contrast, splenic erythropoiesis is increased. Combined Rac1 and Rac2 deficiency compromises proliferation of the megakaryocyte-erythrocyte progenitor population in the bone marrow, while it allows increased survival and proliferation of megakaryocyte-erythrocyte progenitors in the spleen. CONCLUSIONS: These data suggest that Rac1 and Rac2 GTPases are essential for normal bone marrow erythropoiesis but that they are dispensable for erythropoiesis in the spleen, implying different signaling pathways for homeostatic and stress erythropoiesis.